2004
DOI: 10.2202/1548-923x.1035
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Human Simulator for Undergraduate Nurse Education

Abstract: Use of a human patient simulator has been identified as an effective teaching strategy in many areas of the health care field. However, there is little information to help faculty learn the general principles of simulation. This article provides basic concepts to those anticipating simulator use. A guide for running a successful simulation is provided. A heart failure scenario is used as an example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Although SE is a complex phenomenon, it is subjective and thus more items on the SE instrument would not necessarily change the subject's response. Although others have used multiple item SE assessments in HPS (Jarzemsky & McGrath, 2008;Jeffries & Rizzolo, 2006;Lauder et al, 2008;McCausland, Curran, & Cataldi, 2004;Ravert, 2004), they typically are inquiring about a subject's SE in multiple topic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although SE is a complex phenomenon, it is subjective and thus more items on the SE instrument would not necessarily change the subject's response. Although others have used multiple item SE assessments in HPS (Jarzemsky & McGrath, 2008;Jeffries & Rizzolo, 2006;Lauder et al, 2008;McCausland, Curran, & Cataldi, 2004;Ravert, 2004), they typically are inquiring about a subject's SE in multiple topic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Student engagement with the HPS adds a learning dimension not found in traditional didactic teaching methods that normally involve passive learning and emphasize rote memorization, resulting in less retention (Haskvitz & Koop, 2004). Authors of recent descriptive studies on the use of HPS in nursing programs suggested that most students felt that the HPS was realistic and prepared them for clinical situations, although minor technical problems had to be overcome (Feingold, Calaluce, & Kallen, 2004;McCausland, Curran, & Cataldi, 2004;Nehring, Ellis, & Lashley, 2004;Ravert, 2002;Wilson et al, 2005).…”
Section: Current Research On Simulation In Nursing Educationmentioning
confidence: 99%
“…A major documented advantage of patient simulations for nursing students has been the ability to learn interactively and to practice skills in a risk-free environment with immediate faculty feedback (Nehring et al, 2001;Feingold et al, 2004;McCausland et al, 2004;Haskvitz, & Koop, 2004;Rauen, 2004). Other advantages identified in the literature were learning in a self-paced manner, using technology to improve critical thinking skills Rauen, 2004), applying theory to practice in an integrated manner (Rauen, 2004), remediating students experiencing difficulty in clinical situations (Haskvitz & Koop, 2004), and reinforcing curriculum consistency across learners (Ravert, 2002).…”
Section: Current Research On Simulation In Nursing Educationmentioning
confidence: 99%
“…Although the use of a high-fidelity human patient simulator displays benefits and positive outcomes, such as improving students' knowledge (Bogossian et al, 2013) and self-efficacy (Cardoza and Hood, 2012), its high cost with respect to technical and human resources has prompted administrators and faculty to contemplate its value (McCausland et al, 2004). In addition, some studies have reported disadvantages of a high-fidelity human patient simulator, such as the limited number of students that can be trained at one time (Hicks et al, 2009), and negative transfer when the instructor fails to make clear to the students the differences between the training device and the real situation (Bond et al, 2007).…”
Section: Introductionmentioning
confidence: 99%